KERNOHAN’S NOTCH PHENOMENON: REVIEW OF LITERATURE AND CLINICAL LESSONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Kernohan’s notch phenomenon is a rare and paradoxical clinical entity characterized by ipsilateral hemiparesis in the presence of a supratentorial space-occupying lesion. This false localizing sign occurs when an expanding mass causes a midline shift and transtentorial herniation, resulting in the mechanical compression of the contralateral cerebral peduncle against the rigid, free edge of the tentorium cerebelli (Kernohan and Woltman, 1929; Neki et al., 2017). Historically, this phenomenon posed significant diagnostic challenges, often leading to surgical interventions on the wrong side of the cranium (Wolf et al., 1995; Murhega et al., 2023). However, advancements in neuroimaging, particularly magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI), have elucidated the pathophysiological substrate of the condition, revealing structural disruptions and signal changes within the crus cerebri (Yoo et al., 2008; Jang and Pyun, 2013). This review synthesizes current knowledge on the historical background, neuroanatomical basis, pathophysiology, and clinical significance of Kernohan’s notch phenomenon. It explores various etiologies including traumatic brain injury, primary neoplasms, and rare presentations such as spontaneous intracranial hypotension and sickle cell disease (Sasikala et al., 2014; Ozyigit, 2023). Ultimately, prompt radiological identification and surgical decompression are critical for mitigating permanent motor deficits and improving functional outcomes (Beucler et al., 2022; Chauhan et al., 2024).